Meningkatkan Hasil Belajar Siswa Melalui Model Projek Based Learning Dalam Pembelajaran PAI dan Budi Pekerti Di SDN 08 Bukit Malintang - Sari, Nurma (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to examine the implementation of the Project-Based Learning model in improving students’ learning outcomes in Islamic Religious Education at SD Negeri 08 Bukit Malintang. The research used a classroom action research approach conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The results showed that in Cycle I, 80% of students achieved scores above the minimum passing grade (KKM), while in Cycle II, this number increased to 90%. The implementation of the Project-Based Learning model successfully enhanced student participation, encouraged group collaboration, and improved understanding of the material. Based on these results, the Project-Based Learning model proves to be an effective choice for enhancing the quality of classroom instruction.